Graphite felt electrode for vanadium battery and preparation method thereof

By introducing the doping amounts of metals Sn, Ti and Bi on the surface of the graphite felt electrode, and using the preparation method of spinel composite graphite felt electrodes, the problems of low electrode activity and serious side reactions in all vanadium flow batteries are solved, and the battery performance and energy efficiency are improved.

CN119447330BActive Publication Date: 2025-05-09HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510013723.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-05-09
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

In all vanadium flow batteries, the graphite felt electrode has low electrochemical activity and the initial installation cost of the electrolyte is high, which limits the commercial application of vanadium batteries. At the same time, the oxygen evolution/hydrogen evolution side reaction gradually intensifies during battery operation, affecting battery performance.

Method used

By introducing the doping amounts of metals Sn, Ti and Bi on the surface of the graphite felt, and by preparing spinel composite graphite felt electrodes, including heat treatment, electrodeposition, calcination and perovskite inlay, an efficient graphite felt electrode for vanadium batteries is prepared.

Benefits of technology

It effectively inhibits the side reactions of oxygen and hydrogen evolution, improves the utilization rate of electrolyte, reduces the energy loss caused by side reactions during battery operation, and improves the energy efficiency and electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447330B_ABST
    Figure CN119447330B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of all-vanadium liquid flow battery electrodes, and discloses a graphite felt electrode for vanadium battery and a preparation method and application thereof, comprising the following steps: graphite felt pretreatment; preparation of spinel composite graphite felt; preparation of spinel-embedded perovskite composite graphite felt electrode; preparation of composite graphite felt electrode; and synthesis of nano-petal-shaped spinel composite perovskite nanospheres by electroplating + sol-gel method, which have a stable structure, an increased effective active area, catalyze the redox ability of vanadium, reduce the reaction energy barrier, effectively reduce the amount of oxygen and hydrogen released in the electrolyte, inhibit oxygen evolution / hydrogen evolution side reactions, improve the utilization rate of the electrolyte, and reduce the energy loss caused by side reactions during battery operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of all-vanadium liquid flow battery electrodes, and in particular to a graphite felt electrode for a vanadium battery and a preparation method thereof. Background Art

[0002] Among various flow batteries, all-vanadium flow batteries (vanadium batteries for short) are considered to be one of the most promising large-scale energy storage batteries because they reduce the impact of cross-contamination between positive and negative electrode materials, have high electrochemical reversibility, and greatly extend the service life of the electrolyte.

[0003] However, the graphite felt electrodes commonly used in all-vanadium flow batteries have low electrochemical activity, and the high initial installation cost of vanadium electrolytes still limits the commercial application of vanadium batteries. Modification measures such as introducing oxygen-containing functional groups on the graphite felt surface can increase the electrode surface area and improve the electrochemical activity of the positive and negative graphite felt electrodes. However, due to the overlap between the electrolyte redox potential and the oxygen / hydrogen evolution potential, as the battery operates, the oxygen / hydrogen evolution side reactions will gradually intensify, thereby affecting the performance of the battery. Summary of the invention

[0004] The present invention provides a graphite felt electrode for a vanadium battery and a preparation method thereof to overcome the above problems.

[0005] A method for preparing a graphite felt electrode for a vanadium battery comprises the following steps:

[0006] Step S1: placing the graphite felt in an atmosphere furnace for heat treatment, washing the treated graphite felt with 1-3 mol / L hydrochloric acid and ultrapure water, and drying in an oven at 50-70° C. to obtain pretreated graphite felt;

[0007] Step S2: dissolving the metal salt and the stabilizer in 0.5-1 mol / L sulfuric acid as an electrodeposition solution, using the graphite felt pretreated in step S1 as a cathode and nickel foam as an anode to perform electrodeposition to obtain a metal dendrite composite graphite felt, and placing the metal dendrite composite graphite felt in an atmosphere furnace for high-temperature calcination to obtain a spinel composite graphite felt electrode;

[0008] Step S3: dissolve the metal salt in a mixed solution of water and anhydrous ethanol, stir in a water bath at 50-70°C, add a chelating agent, stir for 30 minutes to obtain a reaction solution, add an alkaline solution to adjust the pH value to 6.5-7.5, continue stirring for 0.5h-2h, and naturally cool to room temperature to obtain a gel precursor, soak the spinel composite graphite felt electrode obtained in step S2 in the gel precursor, take it out, place it in a blast drying oven to dry, obtain a precursor, place the precursor in a muffle furnace to calcine, and obtain a spinel-embedded perovskite composite graphite felt electrode.

[0009] Preferably, the heat treatment process in step S1 is: nitrogen atmosphere, keeping at 400-500° C. for 2-4 hours, and a heating rate of 4-8° C. / min.

[0010] Preferably, in step S2, the metal salt is a mixture of tin dichloride and titanium tetrachloride, the total concentration of the metal salt is 0.03-0.3 mol / L, and the molar concentration ratio of tin dichloride: titanium tetrachloride = 2:1; the stabilizer is: any one of ascorbic acid, oxalic acid, citric acid, lactose and fructose, and the molar concentration ratio of metal salt: stabilizer = 1: (0.1-2).

[0011] Preferably, the electrodeposition process in step S2 is: deposition voltage 0.5-5V, deposition time 5-30min; high temperature calcination process is: calcination at 350-450°C for 4-6h in air atmosphere, heating rate 2-6°C / min, cooling rate 2-4°C / min, down to 25°C.

[0012] Preferably, in step S3, the volume ratio of water to anhydrous ethanol in the mixed solution is 1: (5-10); the metal salt is a mixture of lanthanum nitrate and bismuth nitrate, the total concentration of the metal salt is 0.02-0.2 mol / L, and the molar concentration ratio of lanthanum nitrate: bismuth nitrate = 1: 1; the chelating agent is any one of citric acid, EDTA, glycine, and urea, and the molar concentration ratio of metal salt: chelating agent: anhydrous ethanol = 1: (1.1-1.5).

[0013] Preferably, the alkaline solution in step S3 is any one of sodium hydroxide solution, potassium hydroxide solution and ammonia solution, with a concentration of 1-5 mol / L, and the rate of adding the alkaline solution is 5% to 10% of the total volume of the reaction solution per minute.

[0014] Preferably, the drying process in step S3 is: drying at 50-80° C. for 10-24 hours.

[0015] Preferably, the calcination process in step S3 is: calcination at 350-450°C for 4-6h in air atmosphere, with a heating rate of 2-6°C / min and a cooling rate of 2-4°C / min, until the temperature drops to 25°C.

[0016] A graphite felt electrode for a vanadium battery is prepared by using the above-mentioned method for preparing a graphite felt electrode for a vanadium battery.

[0017] The beneficial effects of the present invention are:

[0018] 1. The present invention effectively inhibits the oxygen evolution side reaction by introducing the doping amount of metal Sn and Ti, improves the utilization rate of the electrolyte, and reduces the energy loss caused by the side reaction during battery operation;

[0019] 2. The present invention effectively inhibits the hydrogen evolution side reaction by introducing the doping amount of metal Bi, improves the utilization rate of the electrolyte, and reduces the energy loss caused by the side reaction during battery operation;

[0020] 3. The present invention introduces metal La to stabilize the structure of perovskite during battery operation, which is beneficial to the corrosion resistance and stability of perovskite materials;

[0021] 4. The present invention deposits spinel on the surface of graphite felt and inlays perovskite, which is combined with the physical impregnation method to make it more dense and reliable, and have a higher reaction active area, thereby optimizing the adsorption of vanadium ions in the flow battery, catalyzing the redox ability of vanadium, reducing the reaction energy barrier, and improving the energy efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the graphite felt electrode of Example 1 of the present invention;

[0023] Figure 2 The LSV curve of hydrogen evolution of the graphite felt electrode obtained in Example 1 of the present invention;

[0024] Figure 3 The LSV curve of hydrogen evolution of the graphite felt electrode obtained in Comparative Example 1 of the present invention;

[0025] Figure 4 This is the oxygen evolution LSV curve of the graphite felt electrode obtained in Example 1 of the present invention;

[0026] Figure 5 This is the oxygen evolution LSV curve of the graphite felt electrode obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0028] A method for preparing a graphite felt electrode for a vanadium battery comprises the following steps:

[0029] Step S1: placing the graphite felt in an atmosphere furnace for heat treatment, washing the treated graphite felt with 1-3 mol / L hydrochloric acid and ultrapure water, and drying in an oven at 50-70°C to obtain pretreated graphite felt; the heat treatment process is: nitrogen atmosphere, keeping warm at 400-500°C for 2-4h, and the heating rate is 4-8°C / min.

[0030] Step S2: dissolving a metal salt and a stabilizer in 0.5-1 mol / L sulfuric acid as an electrodeposition solution, using the graphite felt pretreated in step S1 as a cathode and nickel foam as an anode for electrodeposition to obtain a metal dendrite composite graphite felt, placing the metal dendrite composite graphite felt in an atmosphere furnace for high-temperature calcination to obtain a spinel composite graphite felt electrode; the metal salt is a mixture of tin dichloride and titanium tetrachloride, the total concentration of the metal salt is 0.03-0.3 mol / L, and the molar concentration ratio of tin dichloride: titanium tetrachloride is 2:1; the stabilizer is any one of ascorbic acid, oxalic acid, citric acid, lactose and fructose, and the molar concentration ratio of metal salt: stabilizer is 1: (0.1-2). The electro-deposition process is: deposition voltage 0.5-5V, deposition time 5-30min; the high temperature calcination process is: calcination at 350-450°C for 4-6h in air atmosphere, heating rate 2-6°C / min, cooling rate 2-4°C / min, down to 25°C.

[0031] Step S3: dissolve the metal salt in a mixed solution of water and anhydrous ethanol, stir in a water bath at 50-70°C, add a chelating agent, stir for 30 minutes to obtain a reaction solution, add an alkaline solution to adjust the pH value to 6.5-7.5, continue stirring for 0.5h-2h, and naturally cool to room temperature to obtain a gel precursor, soak the spinel composite graphite felt electrode obtained in step S2 in the gel precursor, take it out, place it in a blast drying oven to dry, obtain a precursor, place the precursor in a muffle furnace to calcine, and obtain a spinel-embedded perovskite composite graphite felt electrode. The volume ratio of water to anhydrous ethanol in the mixed solution is 1: (5-10); the metal salt is a mixture of lanthanum nitrate and bismuth nitrate, the total concentration of the metal salt is 0.02-0.2 mol / L, and the molar concentration ratio of lanthanum nitrate: bismuth nitrate = 1: 1; the chelating agent is any one of citric acid, EDTA, glycine, and urea, and the molar concentration ratio of metal salt: chelating agent: anhydrous ethanol = 1: (1.1-1.5). The alkaline solution is any one of sodium hydroxide solution, potassium hydroxide solution, and ammonia solution, with a concentration of 1-5 mol / L, and the rate of adding the alkaline solution is: 5% to 10% of the total volume of the reaction solution per minute. The drying process is: drying at 50-80°C for 10-24h. The calcination process is: calcining at 350-450°C for 4-6h in an air atmosphere, with a heating rate of 2-6°C / min, and a cooling rate of 2-4°C / min, reducing to 25°C.

[0032] Embodiment 1: This embodiment is specifically obtained by the following operations:

[0033] Step S1, graphite felt pretreatment: placing the graphite felt in an atmosphere furnace at 400°C for heat treatment for 4 hours, with a heating rate of 4°C / min, washing the treated graphite felt with 1 mol / L hydrochloric acid and ultrapure water, and drying in an oven at 50°C to obtain pretreated graphite felt.

[0034] Step S2, preparation of spinel composite graphite felt: metal salt and ascorbic acid are mixed and dissolved in 0.5mol / L sulfuric acid to obtain 0.02mol / L tin dichloride, 0.01mol / L titanium tetrachloride and 0.003mol / L ascorbic acid, which are used as electrodeposition solution. The pretreated graphite felt is used as the cathode and the nickel foam is used as the anode for electrodeposition. The deposition parameters are set to a voltage of 0.5V and a time of 30min to obtain Sn / Ti metal dendrite composite graphite felt. The obtained metal dendrite composite graphite felt is placed in an air atmosphere and sintered at 350°C for 6h, with a heating rate of 2°C / min and a cooling rate of 2°C / min to obtain Sn2TiO4 composite graphite felt.

[0035] Step S3, preparation of spinel-embedded perovskite composite graphite felt electrode: ultrapure water and anhydrous ethanol are mixed in a volume ratio of 1:5, lanthanum nitrate and bismuth nitrate are added to obtain a mixed solution of 0.01 mol / L lanthanum nitrate and 0.01 mol / L bismuth nitrate, and stirred in a water bath at 50°C, 0.022 mol / L citric acid is added, and after stirring for 30 minutes, 1 mol / L sodium hydroxide is added at a rate of 5% to 10% of the total volume of the reaction solution per minute, and the pH value of the solution is adjusted to 6.5. After continuous stirring for 0.5 h, the solution is naturally cooled to room temperature to obtain a gel precursor, and the Sn2TiO4 composite graphite felt is immersed in the gel, so that its surface is fully coated with the gel, and then taken out, placed in a blast drying oven and dried at 50°C for 24 h to obtain a precursor, and placed in an air atmosphere for high-temperature sintering at 350°C for 6 h, with a heating rate of 2°C / min and a cooling rate of 2°C / min to obtain LaBiO3 / Sn2TiO4 composite graphite felt.

[0036] Embodiment 2: This embodiment is obtained by the following operations:

[0037] Step S1, graphite felt pretreatment: placing the graphite felt in an atmosphere furnace at 425°C for heat treatment for 3.5 hours, with a heating rate of 5°C / min, washing the treated graphite felt with 3 mol / L hydrochloric acid and ultrapure water, and drying in a 70°C oven to obtain pretreated graphite felt.

[0038] Step S2, preparation of spinel composite graphite felt: metal salt and oxalic acid are mixed and dissolved in 1 mol / L sulfuric acid to obtain 0.06 mol / L tin dichloride, 0.03 mol / L titanium tetrachloride and 0.045 mol / L oxalic acid, which are used as electrodeposition solution. The pretreated graphite felt is used as the cathode and the nickel foam is used as the anode for electrodeposition. The deposition parameters are set to a voltage of 1 V and a time of 20 min to obtain Sn / Ti metal dendrite composite graphite felt. The obtained metal dendrite composite graphite felt is placed in an air atmosphere and sintered at 375°C for 5.5 h, with a heating rate of 3°C / min and a cooling rate of 2.5°C / min to obtain Sn2TiO4 composite graphite felt.

[0039] Step S3, preparation of spinel-embedded perovskite composite graphite felt electrode: ultrapure water and anhydrous ethanol are mixed in a volume ratio of 1:6, lanthanum nitrate and bismuth nitrate are added to obtain a mixed solution of 0.03 mol / L lanthanum nitrate and 0.03 mol / L bismuth nitrate, and the mixture is stirred in a water bath at 55°C, 0.072 mol / L EDTA is added, and after stirring for 30 minutes, 2 mol / L sodium hydroxide is added at a rate of 5% to 10% of the total volume of the reaction solution per minute, and the pH value of the solution is adjusted to 6.8. After continuous stirring for 1 hour, the mixture is naturally cooled to room temperature to obtain a gel precursor, and the Sn2TiO4 composite graphite felt is immersed in the gel, so that its surface is fully coated with the gel, and then taken out, placed in a blast drying oven and dried at 55°C for 22 hours to obtain a precursor, and placed in an air atmosphere for high-temperature sintering at 375°C for 5.5 hours, with a heating rate of 3°C / min and a cooling rate of 2.5°C / min to obtain LaBiO3 / Sn2TiO4 composite graphite felt.

[0040] Embodiment 3: This embodiment is specifically obtained by the following operations:

[0041] Step S1, graphite felt pretreatment: placing the graphite felt in an atmosphere furnace at 450°C for heat treatment for 3 hours, with a heating rate of 6°C / min, washing the treated graphite felt with 2mol / L hydrochloric acid and ultrapure water, and drying in an oven at 60°C to obtain pretreated graphite felt.

[0042] Step S2, preparation of spinel composite graphite felt: metal salt and citric acid are mixed and dissolved in 0.8 mol / L sulfuric acid to obtain 0.1 mol / L tin dichloride, 0.05 mol / L titanium tetrachloride and 0.15 mol / L citric acid as electrodeposition solution, the pretreated graphite felt is used as cathode, nickel foam is used as anode, and electrodeposition is performed, and the deposition parameters are set to voltage 2V and time 15min to obtain Sn / Ti metal dendrite composite graphite felt, and the obtained metal dendrite composite graphite felt is placed in an air atmosphere and sintered at 400°C for 5h, with a heating rate of 4°C / min and a cooling rate of 3°C / min to obtain Sn2TiO4 composite graphite felt.

[0043] Step S3, preparation of spinel-embedded perovskite composite graphite felt electrode: ultrapure water and anhydrous ethanol are mixed in a volume ratio of 1:7, lanthanum nitrate and bismuth nitrate are added to obtain a mixed solution of 0.05 mol / L lanthanum nitrate and 0.05 mol / L bismuth nitrate, and the mixture is stirred in a water bath at 60°C, 0.13 mol / L glycine is added, and after stirring for 30 minutes, 3 mol / L potassium hydroxide is added at a rate of 5% to 10% of the total volume of the reaction solution per minute, and the pH value of the solution is adjusted to 7. After continuous stirring for 1 hour, the mixture is naturally cooled to room temperature to obtain a gel precursor, and the Sn2TiO4 composite graphite felt is immersed in the gel, so that its surface is fully coated with the gel, and then taken out, and dried in a forced air drying oven at 60°C for 18 hours to obtain a precursor, which is placed in an air atmosphere and sintered at 400°C for 5 hours, with a heating rate of 4°C / min and a cooling rate of 3°C / min to obtain LaBiO3 / Sn2TiO4 composite graphite felt.

[0044] Embodiment 4: This embodiment is specifically obtained by the following operations:

[0045] Step S1, graphite felt pretreatment: placing the graphite felt in an atmosphere furnace at 480°C for heat treatment for 2.5 hours, with a heating rate of 7°C / min, washing the treated graphite felt with 2mol / L hydrochloric acid and ultrapure water, and drying in a 50°C oven to obtain pretreated graphite felt.

[0046] Step S2, preparation of spinel composite graphite felt: metal salt and lactose are mixed and dissolved in 0.6 mol / L sulfuric acid to obtain 0.14 mol / L tin dichloride, 0.07 mol / L titanium tetrachloride and 0.32 mol / L lactose, which are used as electrodeposition solution. The pretreated graphite felt is used as the cathode and the nickel foam is used as the anode for electrodeposition. The deposition parameters are set to a voltage of 3 V and a time of 10 min to obtain Sn / Ti metal dendrite composite graphite felt. The obtained metal dendrite composite graphite felt is placed in an air atmosphere and sintered at 425°C for 4.5 h, with a heating rate of 5°C / min and a cooling rate of 3.5°C / min to obtain Sn2TiO4 composite graphite felt.

[0047] Step S3, preparation of spinel-embedded perovskite composite graphite felt electrode: ultrapure water and anhydrous ethanol are mixed in a volume ratio of 1:8, lanthanum nitrate and bismuth nitrate are added to obtain a mixed solution of 0.08 mol / L lanthanum nitrate and 0.08 mol / L bismuth nitrate, and the mixture is stirred in a water bath at 65°C, 0.23 mol / L urea is added, and after stirring for 30 minutes, 4 mol / L ammonia water is added at a rate of 5% to 10% of the total volume of the reaction solution per minute, the pH value of the solution is adjusted to 7.2, and the mixture is stirred for 1.5 hours and then naturally cooled to room temperature to obtain a gel precursor, and the Sn2TiO4 composite graphite felt is immersed in the gel, so that its surface is fully coated with the gel, and then taken out, and placed in a blast drying oven at 70°C for 14 hours to obtain a precursor, which is placed in an air atmosphere and sintered at 425°C for 4.5 hours, with a heating rate of 5°C / min and a cooling rate of 3.5°C / min to obtain LaBiO3 / Sn2TiO4 composite graphite felt.

[0048] Embodiment 5: This embodiment is specifically obtained by the following operations:

[0049] Step S1, graphite felt pretreatment: placing the graphite felt in an atmosphere furnace at 500°C for heat treatment for 2h, with a heating rate of 8°C / min, washing the treated graphite felt with 2mol / L hydrochloric acid and ultrapure water, and drying in an oven at 50°C to obtain pretreated graphite felt.

[0050] Step S2, preparation of spinel composite graphite felt: metal salt and fructose are mixed and dissolved in 0.5 mol / L sulfuric acid to obtain 0.2 mol / L tin dichloride, 0.1 mol / L titanium tetrachloride and 0.6 mol / L fructose, which are used as electrodeposition liquid. The pretreated graphite felt is used as the cathode and the nickel foam is used as the anode for electrodeposition. The deposition parameters are set to a voltage of 5 V and a time of 5 min to obtain Sn / Ti metal dendrite composite graphite felt. The obtained metal dendrite composite graphite felt is placed in an air atmosphere and sintered at 450°C for 4 h, with a heating rate of 6°C / min and a cooling rate of 4°C / min to obtain Sn2TiO4 composite graphite felt.

[0051] Step S3, preparation of spinel-embedded perovskite composite graphite felt electrode: ultrapure water and anhydrous ethanol are mixed in a volume ratio of 1:10, lanthanum nitrate and bismuth nitrate are added to obtain a mixed solution of 0.1 mol / L lanthanum nitrate and 0.1 mol / L bismuth nitrate, and the mixture is stirred in a water bath at 70°C, 0.3 mol / L starch is added, and after stirring for 30 minutes, 5 mol / L ammonia water is added at a rate of 5% to 10% of the total volume of the reaction solution per minute, the pH value of the solution is adjusted to 7.5, and the mixture is stirred for 2 hours and then naturally cooled to room temperature to obtain a gel precursor, and the Sn2TiO4 composite graphite felt is immersed in the gel, so that its surface is covered with gel, and then taken out, and dried in a forced air drying oven at 80°C for 10 hours to obtain a precursor, which is placed in an air atmosphere and sintered at 450°C for 4 hours, with a heating rate of 6°C / min and a cooling rate of 4°C / min to obtain LaBiO3 / Sn2TiO4 composite graphite felt.

[0052] Comparative Example 1:

[0053] This comparative example is a blank control group, that is, untreated graphite felt is used as the electrode.

[0054] Comparative Example 2:

[0055] The preparation process of this comparative example is different from that of Example 1 only in that step S3 is not performed.

[0056] Comparative Example 3:

[0057] The preparation process of this comparative example is different from that of the embodiment only in that step S2 is not performed.

[0058] Comparative Example 4:

[0059] The preparation process of this comparative example is different from that of Example 1 only in that: in step S3, LaBiO3 is first sintered and then dispersed into a 5wt% perfluorosulfonic acid resin solution, and immersed in an environment of 20°C for 12 hours to obtain an impregnation solution; the graphite felt obtained after pretreatment is immersed in the impregnation solution, and LaBiO3 is bonded to the surface of the Sn2TiO4 composite graphite felt by a physical impregnation method.

[0060] The graphite felts prepared in Examples 1-5 and Comparative Examples 1-4 were assembled into battery stacks and subjected to charge and discharge tests under the same test conditions, and the battery coulombic efficiency, voltage efficiency, energy efficiency, and discharge capacity were recorded. The test results are shown in Table 1:

[0061] Table 1 Test results of electrode performance of examples and comparative examples

[0062] Coulomb efficiency Voltage efficiency Energy efficiency Discharge capacity (Ah) Example 1 96.7% 91.8% 88.8% 4.12 Example 2 96.5% 91.5% 88.3% 4.08 Example 3 96.8% 91.0% 88.1% 4.11 Example 4 96.5% 91.5% 88.3% 4.08 Example 5 96.5% 91.6% 88.4% 4.09 Comparative Example 1 96.1% 89.1% 85.7% 3.81 Comparative Example 2 96.3% 90.5% 87.1% 3.92 Comparative Example 3 96.5% 90.8% 87.6% 4.03 Comparative Example 4 96.4% 90.5% 87.2% 3.97

[0063] As can be seen from Table 1, Examples 1-5 have higher energy, voltage efficiency and discharge capacity than Comparative Example 1, indicating that the present invention effectively improves the reaction activity of the electrode, and simultaneously inhibits the side reactions of hydrogen evolution in the negative electrode electrolyte and oxygen evolution in the positive electrode electrolyte, and Figure 1 It can be seen that the three-dimensional material LaBiO3 / Sn2TiO4 has a higher reactive area, optimizes the adsorption of vanadium ions in the flow battery, catalyzes the redox ability of vanadium, reduces the reaction energy barrier, and improves the energy efficiency of the battery. Figure 2-Figure 5 It can be seen that at the same potential, the hydrogen evolution current density and oxygen evolution current density in the graphite felt electrode LSV curve obtained in Example 1 are both smaller than those in Comparative Example 1, which further illustrates that metal Sn, Ti and Bi can effectively inhibit oxygen evolution / hydrogen evolution side reactions. Example 1 is compared with Comparative Example 2, and has higher energy, voltage efficiency and discharge capacity, indicating that the introduction of the doping amount of metal Sn and Ti effectively inhibits the oxygen evolution side reaction, improves the utilization rate of the electrolyte, and reduces the energy loss caused by the side reaction during battery operation. Example 1 is compared with Comparative Example 3, and has higher energy, voltage efficiency and discharge capacity, indicating that the introduction of the doping amount of metal Bi effectively inhibits the hydrogen evolution side reaction, improves the utilization rate of the electrolyte, and reduces the energy loss caused by the side reaction during battery operation. The introduction of metal La makes the perovskite structurally stable during battery operation, which is beneficial to the corrosion resistance and stability of the perovskite material, further illustrating that the present invention can effectively inhibit the hydrogen evolution side reaction by Bi doping. Compared with Example 1 and Comparative Example 4, Example 1 has higher energy efficiency and voltage efficiency, which shows that the present invention deposits spinel on the surface of graphite felt and embeds perovskite, which is more dense and reliable when combined with the physical impregnation method.

[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a graphite felt electrode for a vanadium battery, characterized in that: The steps include: Step S1: placing the graphite felt in an atmosphere furnace for heat treatment, washing the treated graphite felt with 1-3 mol / L hydrochloric acid and ultrapure water, and drying in an oven at 50-70° C. to obtain pretreated graphite felt; Step S2: dissolving the metal salt and the stabilizer in 0.5-1 mol / L sulfuric acid as an electrodeposition solution, using the graphite felt pretreated in step S1 as a cathode and nickel foam as an anode for electrodeposition to obtain a metal dendrite composite graphite felt, placing the metal dendrite composite graphite felt in an atmosphere furnace for high-temperature calcination to obtain a spinel composite graphite felt electrode; the metal salt is a mixture of tin dichloride and titanium tetrachloride, the total concentration of the metal salt is 0.03-0.3 mol / L, and the molar concentration ratio of tin dichloride: titanium tetrachloride is 2:1; Step S3: dissolving the metal salt in a mixed solution of water and anhydrous ethanol, stirring in a water bath at 50-70°C, adding a chelating agent, stirring for 30 minutes to obtain a reaction solution, adding an alkaline solution to adjust the pH value to 6.5-7.5, stirring continuously for 0.5h-2h, and naturally cooling to room temperature to obtain a gel precursor, soaking the spinel composite graphite felt electrode obtained in step S2 in the gel precursor, taking it out, placing it in a blast drying oven to dry, obtaining a precursor, placing the precursor in a muffle furnace to calcine, and obtaining a spinel-embedded perovskite composite graphite felt electrode; The volume ratio of water to anhydrous ethanol is 1:(5-10); the metal salt is a mixture of lanthanum nitrate and bismuth nitrate, the total concentration of the metal salt is 0.02-0.2 mol / L, and the molar concentration ratio of lanthanum nitrate: bismuth nitrate is 1:1; the chelating agent is any one of citric acid, EDTA, glycine, and urea, and the molar concentration ratio of metal salt: chelating agent: anhydrous ethanol is 1:(1.1-1.5); the calcination process is: calcination at 350-450°C for 4-6h in an air atmosphere, the heating rate is 2-6°C / min, the cooling rate is 2-4°C / min, and the temperature is reduced to 25°C.

2. The method for preparing a graphite felt electrode for a vanadium battery according to claim 1, characterized in that: The heat treatment process in step S1 is: nitrogen atmosphere, 400-500° C. for 2-4 hours, and a heating rate of 4-8° C. / min.

3. The method for preparing a graphite felt electrode for a vanadium battery according to claim 1, characterized in that: In step S2, the stabilizer is any one of ascorbic acid, oxalic acid, citric acid, lactose and fructose, and the molar concentration ratio of metal salt: stabilizer is 1: (0.1-2).

4. The method for preparing a graphite felt electrode for a vanadium battery according to claim 1, characterized in that: The electro-deposition process in step S2 is: deposition voltage 0.5-5V, deposition time 5-30min; high temperature calcination process is: calcination at 350-450°C for 4-6h in air atmosphere, heating rate 2-6°C / min, cooling rate 2-4°C / min, down to 25°C.

5. The method for preparing a graphite felt electrode for a vanadium battery according to claim 1, characterized in that: The alkaline solution in step S3 is any one of sodium hydroxide solution, potassium hydroxide solution and ammonia solution, with a concentration of 1-5 mol / L, and the rate of adding the alkaline solution is: 5% to 10% of the total volume of the reaction solution per minute.

6. The method for preparing a graphite felt electrode for a vanadium battery according to claim 1, characterized in that: The drying process in step S3 is: drying at 50-80° C. for 10-24 hours.

7. A graphite felt electrode for a vanadium battery, wherein the graphite felt electrode is prepared by the method for preparing a graphite felt electrode for a vanadium battery as claimed in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Anode material loaded with spinel material and preparation method and application thereof

    CN115064713A

  • Method for prolonging service life of vanadium redox flow battery electrode

    CN115602859A

  • Preparation method and application of metal element modified graphite felt electrode

    CN118352543A